2005
DOI: 10.1016/j.jalz.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Ways toward an early diagnosis in Alzheimer's disease: The Alzheimer's Disease Neuroimaging Initiative (ADNI)

Abstract: With the increasing life expectancy in developed countries, the incidence of Alzheimer's disease (AD) and thus its socioeconomic impact are growing. Increasing knowledge over the last years about the pathomechanisms involved in AD allow for the development of specific treatment strategies aimed at slowing down or even preventing neuronal death in AD. However, this requires also that (1) AD can be diagnosed with high accuracy, because non-AD dementias would not benefit from an AD-specific treatment; (2) AD can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
753
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,004 publications
(787 citation statements)
references
References 112 publications
4
753
0
3
Order By: Relevance
“…The Alzheimer's Disease Neuroimaging Initiative (ADNI), is a multi-institutional, longitudinal neuroimaging biomarker study of 800 elderly patients comprising 200 elderly controls, 400 patients with prodromal AD or amnestic mild cognitive impairment (MCI), and 200 patients with early stage AD [16]. The planning stages of ADNI gathered some of the foremost experts in quantitative neuroimaging of AD to discuss ways of overcoming the technological hurdles of performing precise vMRI across multiple sites and scanner models [7].…”
Section: The Alzheimer's Disease Neuroimaging Initiativementioning
confidence: 99%
“…The Alzheimer's Disease Neuroimaging Initiative (ADNI), is a multi-institutional, longitudinal neuroimaging biomarker study of 800 elderly patients comprising 200 elderly controls, 400 patients with prodromal AD or amnestic mild cognitive impairment (MCI), and 200 patients with early stage AD [16]. The planning stages of ADNI gathered some of the foremost experts in quantitative neuroimaging of AD to discuss ways of overcoming the technological hurdles of performing precise vMRI across multiple sites and scanner models [7].…”
Section: The Alzheimer's Disease Neuroimaging Initiativementioning
confidence: 99%
“…A recent study by Rajan et al has shown that impairment in cognition starts almost 18 years before AD dementia could be clinically diagnosed 4. The distinction between memory decline due to the normal course of aging and early stage AD dementia is so ambiguous that the category of mild cognitive impairment (MCI) has been developed to better characterize the earliest signs of AD 5. The MCI category was initially created to identify the early stages of AD and was primarily based on impairment in memory, but with the advances in research made over time, it was noticeable that some patients with MCI remain stable while others progress to AD 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, future methodological developments should be increasingly based on large datasets and multi-centric studies to increase both reproducibility and predictability. Recent data sharing initiatives such as ADNI (Mueller et al 2005), in combination with cloud-computing power, will provide the necessary prerequisites for these developments. We will hopefully see new advances in individual-level classification analysis in order to provide earlier and more accurate diagnoses, better estimation of prognosis, and eventually improve patient care.…”
Section: Discussionmentioning
confidence: 99%